Real-world experience with the cusp overlap deployment technique for procedural optimization during self-expanding transcatheter aortic valve implantation: our city best practice trial. (14th October 2021) - Maier, O; Binneboessel, S; Klein, K; Piayda, K; Polzin, A; Westenfeld, R; Jung, C; Berisha, N; Zeus, T; Kelm, M; Veulemans, V
Abstract: Background: Aortic valve stenosis treated by transcatheter aortic valve implantation (TAVI) is a fast-growing section in interventional cardiology. Optimal implantation depth (ID) of self-expanding TAVI devices is an important condition for hemodynamic and clinical outcomes. The cusp overlap technique (COT) offers optimized fluoroscopic projections for TAVI with self-expanding devices due to improved anatomic discrimination by elongation of the left ventricular outflow tract and isolation of the non-coronary cusp (NCC) for better assessment of ID. Purpose: This single-center observational study aims to investigate short-term clinical performance, safety, and efficiency outcomes regarding optimized ID in patients undergoing transfemoral TAVI with self-expanding prostheses and COT. Methods: From September 2020 to December 2020, a total of 71 patients underwent TAVI with a newer-generation self-expanding device and COT. The optimal fluoroscopic projection was generated by overlapping the right (RCC) and left coronary cusps (LCC) on the multidetector computed tomography annular plane. Final ID was assessed by the arithmetic mean of distances measured from NCC and LCC to the distal prosthesis end. Outcomes were compared with a control cohort of 339 patients who underwent TAVI from January 2016 to August 2020 with a three-cusp coplanar view only during valve deployment. Results: ID was significantly reduced in the COT cohort (4.3±1.9 vs. 5.0±2.3 mm; p=0.012) with better achievement of optimal ID (2–4 mm) (63.4% vs. 49.9%; p=0.03) and optimization of delta NCC-LCC ID symmetry (1.4±1.3 vs. 1.7±1.3 mm; p=0.026). The rate of pacemaker implantation following TAVI could be reduced (9.9% vs. 19.4%; p=0.05). Six of the seven patients receiving pacemaker in the COT cohort (85.7%) showed ID above membranous septum length. COT resulted in notably higher rates of device repositioning by recapturing (57.8% vs. 16.2%; p<0.001) compared to control cohort. Though, procedure time was prolonged in the COT cohort (82.0±26.5 vs. 74.9±27.5 min; p=0.05) while radiation dose and amount of contrast medium did not differ between the cohorts. No difference was observed in hemodynamic outcomes regarding transvalvular pressure gradients and at least moderate paravalvular leak. Patients implanted with COT had a shorter length of hospital stay (7.1±6.0 vs. 10.3±6.8 days; p<0.001), possibly due to a lower complication rate regarding new conduction disturbances and pacemaker implantation. Conclusion: TAVI using the cusp overlap deployment technique is associated with an optimized implantation depth and a low rate of procedural complications. Therefore, a reduction of new pacemaker implantations and shortened length of hospital stay could be achieved. Funding Acknowledgement: Type of funding sources: None.